Does Public Insurance Crowd out Private Insurance? - Cutler, D. M.; Gruber, J. (Quarterly Journal of Economics, 1996)
The cost of expanding public sector health programs depends critically on the extent to which public eligibility will cover just the uninsured, or will crowd out existing private insurance coverage. We estimate the extent of crowd-out arising from the expansions of Medicaid to pregnant women and children over the 1987–1992 period. We estimate that approximately 50 percent of the increase in Medicaid coverage was associated with a reduction in private insurance coverage. This occurred largely because employees took up employer-based insurance less frequently. There is also some evidence that employers contributed less for insurance and that workers dropped coverage of dependents.